Hubungan antara Homesickness dengan Motivasi Belajar pada Mahasiswa Rantau di Universitas Sebelas Maret - Nikka Azzahra Syawalaufa; Rahma Saniatuzzulfa (Faculty of Ushuluddin and Humanities, 2024)
Overseas students tend to have low learning motivation. One of the internal factors that influences it is spiritual condition. Homesickness is a form of spiritual condition that influences learning motivation. This research aims to determine the relationship between homesickness and learning motivation in overseas students at Sebelas Maret University. The subjects of this research were 100 active students at Sebelas Maret University, Surakarta, who had migrated and lived in boarding houses to study. The sampling technique in this research used purposive sampling. The data collection method uses a measuring instrument consisting of two adapted scales, namely the Motivated Strategies for Learning Questionnaire (α=0.919) and the Homesickness Questionnaire (α=0.885). Data analysis was carried out using product moment correlation using SPSS 25 for Windows. Based on the results of the correlation test, the correlation value between homesickness and learning motivation was -0.234 with p=0.019 (p<0.05). Thus, it can be said that the hypothesis which states that there is a relationship between homesickness and learning motivation in overseas students at Sebelas Maret University can be accepted. This means that the higher the homesickness, the lower the learning motivation, conversely, the lower the homesickness, the higher the learning motivation. This means that students who have homesickness may have low motivation to study. Keywords: homesickness, learning motivation, overseas students